Inheritances, Intergenerational Transfers, and the Accumulation of Health - Carman, Katherine Grace (American Economic Review, 2013)
This paper considers the mechanisms behind a positive correlation between inheritances and health. First, there may merely be a correlation: those from families with enough wealth to provide an inheritance tend to have better health. Second, financial resources could be used to purchase inputs to health. Third, bequests may signal a stronger interest in one's child. This reminder to the child could improve their emotional well-being. On average, the positive correlation suggests merely correlation. However, among subsets of the population, particularly men and those expecting to receive an inheritance, there is a causal relationship likely driven by the third mechanism.